A Proposal to Reform Slot Allocation at Capacity-Constrained Commercial Airports - Andreas Knorr; Alexander Eisenkopf (Wirtschaftsdienst)
Abstract Air transport services require complementary ground and air infrastructure. Capacity constraints of an airport’s runway system create a significant bottleneck. The right of use depends on the availability of a slot. When the demand for slots exceeds the supply, an allocation process is required. In most countries of the world, there is no market mechanism for this. A grandfather clause restricts entry for new entrants at congested airports. A remedy can be found in a property rights perspective.